Marriage of convenience : Rockefeller International Health and revolutionary Mexico - Birn, Anne-Emanuelle, 1964- (Rochester studies in medical history, 2006)
"Transcending standard hagiographic accounts as well as simplistic arguments of cultural imperialism, Marriage of Convenience offers a nuanced analysis of the interaction between the foundation's International Health Division and the Departamento de Salubridad Publica as they jointly promoted public health through campaigns against yellow fever and hookworm disease, organized cooperative rural health units, and educated public health professionals in North American universities and Mexican training stations." "Drawing from a wealth of archival sources in both Mexico and the United States, Birn uncovers the complex give-and-take of this early experience of international health cooperation."--Jacket